Методичні підходи до класифікації загроз для фінансової безпеки суб’єктів господарювання в умовах турбулентної економіки - Утенкова, Каріна; Utenkova, Karina (Дніпро : Дніпровський державний аграрно-економічний університет, 2024)
Метою статті є визначення змісту загроз для фінансової безпеки суб’єктів господарювання в умовах турбулентної економіки та обґрунтування підходів до їх класифікації. Для вирішення визначених завдань у процесі дослідження використано загальнонаукові та спеціальні методи, а саме: діалектичний метод пізнання економічних явищ, принципи економічної теорії щодо сутності і змісту загроз для фінансової безпеки; методи теоретичного узагальнення та порівняння використовувались у процесі опрацювання літературних джерел та вивчення поставлених питань; абстрактно-логічний для теоретичного узагальнення висновків та аналізу результатів дослідження. У статті досліджено сутність дестабілізувальних чинників фінансової безпеки на мікрорівні. Розглянуто сучасний дискурс класифікації загроз для фінансової безпеки суб’єктів господарювання. За період воєнного стану економіка України зазнала серйозних, а під час і безповоротних, втрат матеріальних, трудових і фінансових ресурсів, структурних перетворень в галузях виробництва. Наслідком цього є суттєве зниження прибутковості і рентабельності підприємств. Cучасні тенденції, характерні для економіки України, вимагають ретельного перегляду переліку загроз, визначеного у чинній нормативній базі з питань регулювання національної безпеки, з урахуванням системних та додатково набутих загроз у розрізі функціональних складових економічної безпеки, зокрема фінансової. Важливого значення набуває система своєчасного виявлення та запобігання загрозам для фінансової безпеки, яка повинна ґрунтуватися на всебічному аналізі цих загроз і дозволить застосовувати найбільш дієві механізми протидії їм. Практичне значення одержаних результатів полягає в тому, що вони є базою для подальшого дослідження проблем забезпечення фінансової безпеки.

The purpose of the article is to determine the content of threats to the financial security of economic entities in the conditions of a turbulent economy and to substantiate the approaches to their classification. In order to solve the identified tasks, general scientific and special methods have been used in the research process, including: the dialectical method of understanding economic phenomena, the principles of economic theory regarding the essence and content of threats to financial security; methods of theoretical generalization and comparison have been used in the process of processing literary sources and studying questions; abstract-logical for theoretical generalization of conclusions and analysis of research results. The article examines the essence of the destabilizing factors of financial security at the micro level. The modern discourse of the classification of threats to the financial security of economic entities have been considered. During the period of war time, the economy of Ukraine underwent serious, and at the same time irreversible, losses of material, labour and financial resources, structural transformations in the fields of production. The consequence of it is a significant decrease in the profitability and enterprises efficiency. Modern trends, characteristic of the economy of Ukraine, require a careful review of the list of threats defined in the current regulatory base for the regulation of national security, taking into account systemic and additionally acquired threats in terms of functional components of economic security, particularly financial. The obtained scientific results made it possible to solve certain aspects of important scientific task, which is of exceptional importance for the development of financial security research. In particular, the content of such destabilizing factors as threats, risks and dangers, as well as the classification of threats, has been clarified. The system of timely detection and prevention of threats to financial security becomes important, which should be based on a comprehensive analysis of these threats and will allow the use of the most effective mechanisms for counteracting them. The use of the detailed classification of threats for the formation of a methodological basis for research in the field of financial security is substantiated.
Methodical approaches to the classification of threats to the financial security of economic entities in the conditions of a turbulent economy
Keywords: SOCIAL SCIENCES::Business and economics; фінансова безпека; економічна безпека; підприємства; financial security; economic security